2007
DOI: 10.1007/s10517-007-0179-7
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of low-doses of antibodies to S-100 protein on the formation of long-term sensitization in Helix lucorum

Abstract: Injection of antibodies to Ca-binding protein S-100 in a dilution of 10(-12) before the formation of long-term sensitization in Helix lucorum (10 min before the first electric shock) prevented the increase in defense reactions of pneumostome closure and ommatophore withdrawal. Thus, we demonstrated a protective effect of low-dose antibodies to S-100 on the formation of long-term sensitization as a neurobiological model of anxiety and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…An animal experiment has observed that S100 protein‐deficient male mice exhibit increased exploratory activity and reduced anxiety‐related responses 20 . Meanwhile, another animal experiment showed that low‐dose antibodies to S‐100 protein have protective effects on the formation of long‐term sensitization which is considered a neurobiological model of anxiety 21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An animal experiment has observed that S100 protein‐deficient male mice exhibit increased exploratory activity and reduced anxiety‐related responses 20 . Meanwhile, another animal experiment showed that low‐dose antibodies to S‐100 protein have protective effects on the formation of long‐term sensitization which is considered a neurobiological model of anxiety 21 …”
Section: Introductionmentioning
confidence: 99%
“…20 Meanwhile, another animal experiment showed that low-dose antibodies to S-100 protein have protective effects on the formation of long-term sensitization which is considered a neurobiological model of anxiety. 21 However, no clinical study focused on the association between anxiety symptoms after acute stroke and S-100β has been done. Given the involvement of S-100β in anxiety and the acknowledged elevated serum levels of S-100β in acute stroke patients, 19,22 we aimed to examine whether there is an association between the elevated serum S-100β levels and the development of PSA.…”
Section: Introductionmentioning
confidence: 99%